Comparison of Xpert MTB/RIFAssay with smear microscopy and culture for the detection of pulmonary tuberculosis - Ahmed, Mohammad Tanvir (BRAC University, 2018)
This dissertation is submitted in Partial Fulfillment of the Requirements’ for the Degree of Master of Science in Biotechnology 2017.